2016
DOI: 10.11648/j.sjph.20160405.17
|View full text |Cite
|
Sign up to set email alerts
|

Parental Satisfaction and Barriers Affecting Immunization Services in Rural Communities: Evidence from North Ethiopia

Abstract: Abstract:The purpose of this study was to examine barriers affecting client satisfaction with immunization services rendered in rural district, Ethiopia. A total of 419 caretakers who accessed the service were included and assessed for their satisfaction level using a pretested questionnaire that contained socioeconomic, demographic information, knowledge and various items related to process, service and accessibility factors on immunization service. The response rate was 99.3% and nearly two third of caretake… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
9
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 8 publications
9
9
1
Order By: Relevance
“…Furthermore, in this study, shorter service waiting time (i.e., less than 30 minutes) to get vaccination was another significant predictor for maternal satisfaction towards childhood immunization service. The result is in line with the study finding from Jigjiga [14] and Kombolcha [13] of Ethiopia and Nigeria [38]. As shorter service waiting times might be linked with better accessibility of care and quality service provision, it could increase the satisfaction of mothers towards childhood immunization service and enhance the utilization of health services provided by the health center.…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…Furthermore, in this study, shorter service waiting time (i.e., less than 30 minutes) to get vaccination was another significant predictor for maternal satisfaction towards childhood immunization service. The result is in line with the study finding from Jigjiga [14] and Kombolcha [13] of Ethiopia and Nigeria [38]. As shorter service waiting times might be linked with better accessibility of care and quality service provision, it could increase the satisfaction of mothers towards childhood immunization service and enhance the utilization of health services provided by the health center.…”
Section: Discussionsupporting
confidence: 87%
“…Moreover, the current study showed that information provision about the current vaccine was also another significant predictor of satisfaction to childhood immunization service. This finding is consistent with the study findings done in Jigjiga [14] and Kombolcha [13] of Ethiopia, Ilorin, north-central Nigeria [38], and India [50].…”
supporting
confidence: 93%
See 3 more Smart Citations